Knowledge, attitude and practice of fever and febrile illness among parents of under five children - Mallick, Achinta K.R.; Kumar, Shalu S.; Bangari, Janki; Suyal, Himani (International Journal of Contemporary Pediatrics, 2019)
Background: Fever in children is the commonest cause for outpatient and inpatient admissions in the health care setup. Though most fever episodes are benign with self-limiting course, it is often a reason for anxiety and concerning for parents. The aim of the study was to assess the parental knowledge, attitude and practice regarding fever in children under five years of age. Methods: A cross-sectional question based survey, conducted in the pediatric department of a peripheral hospital in Pune, Maharashtra from parents of under five children, presenting for any consultation from July 2018 to December 2018. Results: There were 636 respondents who completed the study. 38.1% were males. Mean age of responders was 26.85 years (SD 5.12 Range 18 to 37 years). Most of the population were educated lot. 55.5% responders defined fever correctly. There was a huge gap in the parent’s knowledge attitude and practice in fever and it’s management. Lack of information and fear of any untoward incident occurring due to fever were the reason for parental anxiety, frequent medication & combination antipyretic use, and pressure on part of health professionals to increase antibiotic prescriptions. Conclusions: Lack of parental knowledge of fever and fever management in younger children is of concern in the community in spite of improvement in the educational level of parents. There is a utmost need to spread awareness in the community about the benign and the self-limiting nature of most febrile illnesses.